A Review on Smart Car Parking System (Global Journals of Research in Engineering, 2022)
Nowadays vehicle parking has become an important issue and the need is increasing day by day. Growing population in metro cities is leading to huge vehicle density, the problems for car parking has become an unending question. In India we are still using a manual vehicle parking system and that is why we are struggling with the waste of time and fuel problem. When we need to park our car, we need to park our car. The conventional parking systems do not have any intelligent monitoring arrangement; causing wastage of time to find the slot and traffic on the way to park. Conditions are worse when there are multiple lanes and multiple parking slots. In this paper, we present an incisive overview of different methods and tools used in implementation of smart parking systems. There are different approaches being researched upon by people including using IOT, different sensors, cloud or deep learning as well and all the different approaches being used by people have been mentioned in this paper.The paper presents a comparison of all the pros and cons for the approaches being presented by authors in different research papers.
Keywords: vehicle detection; tracking; parking; sensors; cars